A10.22 Response to MTX Plus Prednisone in Camera II Using a Multi-Biomarker Disease Activity (Vectra™DA) TEST and DAS28-ESR. (25th February 2013) - Bijlsma, JWJ; Jurgens, MS; Jacobs, JWG; Bakker, M; Lafeber, FPJ; Welsing, PMJ; Cavet, G; Chernoff, D; Sasso, EH; Li, W; Haney, DJ
Abstract : Background and Objectives: The CAMERA II study (Computer Assisted Management in Early RA) demonstrated that the addition of prednisone versus placebo to a MTX-based tight-control strategy increased effectiveness of therapy and reduced need for biological treatment. The present study evaluated changes in biomarker levels over time with MTX+placebo and MTX+prednisone treatment, using the Multi-Biomarker Disease Activity (MBDA) blood test. Materials and Methods: Clinical and biomarker assessments were performed at monthly visits to 1 year for 92 patients who had MBDA test results available at baseline and ≥1 subsequent visit. Average number of visits with non-missing disease activity measures was 3.7 per patient. Concentrations of 12 serum biomarkers were combined to produce a score between 1 and 100 using the MBDA algorithm, which generates a validated measure of disease activity. Biomarker responses were also assessed individually but only to 5 months, to avoid subsequent protocol-mandated exposures to non-MTX DMARDs for insufficient responders. Association between DAS28-ESR response and MBDA response was assessed using Spearman's correlation. Changes from baseline and comparisons of change over time for MTX+placebo versus MTX+prednisone were analysed by t-tests. Biomarker concentrations were analysed as fractions relative to baseline using Mann Whitney U tests. Results: Changes from baseline to 1 year in DAS28-ESR and MBDA scores showed a significant correlation in the MTX+placebo arm (r = 0.57, p < 0.001, n = 31) and the MTX+prednisone arm (r = 0.57, p = 0.002, n = 28). Improvements in DAS28-ESR (p < 0.001) and MBDA (p = 0.01) scores were observed as early as 1 month post-BL in the MTX+prednisone arm. Significant reduction in disease activity in the MTX+placebo arm was first observed at 2 months for DAS28-ESR (p = 0.02) and 4 months for MBDA (p = 0.03). Overall, DAS28-ESR and MBDA response profiles were similar, with mean changes at month 5 for MTX+placebo and MTX+prednisone being –2.2/–4.2 for DAS28-ESR, and –13/–21 for MBDA score. Individual biomarker response profiles differed: for some biomarkers, MTX+placebo had little/no effect but MTX+prednisone had significant effect (e.g., MMP-1, TNF-R1, VCAM-1); for others, MTX+placebo had a significant effect that was augmented (e.g., CRP, IL-6, VEGF) or not affected (SAA) by prednisone. Conclusions: Responses assessed with the biomarker-based MBDA test and DAS28-ESR were greater and more rapid for therapy with MTX+prednisone than MTX+placebo, even though individual biomarkers differed in their response profiles. The MBDA test may be useful in combination with clinical assessment to evaluate early response to therapy with MTX or MTX+prednisone.